(untitled) (Entrepreneurship Journal for Finance and Business, 2024)
Abstract: Iraq has witnessed in recent years a clear and widespread Iraq has witnessed in recent years a clear and widespread spread of drugs, as evidenced by what is being reported by government agencies such as the Ministry of Health, security services and the media, as some official sources reveal frightening numbers regarding the number of drug users, reaching approximately 40% to 50% of uneducated youth or school students between the ages of 15-35, who are from families with a low standard of living. Accordingly, universities, schools and relevant ministries have begun to warn against this scourge through seminars, conferences, guidance and awareness. Drugs are one of the phenomena that directly affect the structure of Iraqi society in all aspects, whether economic, security, health, political or cultural. Therefore, it is necessary to confront and combat them to limit their impact and eliminate them once and for all, by knowing the reasons that lead to the use of this dangerous phenomenon due to its social and psychological effects that lead the addict to difficulty in doing work, disordered thinking and difficulty communicating with others without a narcotic substance and other matters. Accordingly, it is necessary to It should not be dealt with individually, but rather collectively through political, economic, cultural, security and media cooperation to confront this scourge because of its impact on society as a whole.